The CERN-MEDICIS Isotope Separator Beamline - Martinez Palenzuela, Yisel; Barozier, Vincent; Chevallay, Eric; Cocolios, Thomas E.; Duchemin, Charlotte; Fernier, Pascal; Huyse, Mark; Lambert, Laura; Lopez, Roberto; Marzari, Stefano; Ramos, Joao P.; Stora, Thierry; et al. (Frontiers in Medicine, 2021)
CERN-MEDICIS is an off-line isotope separator facility for the extraction of radioisotopes from irradiated targets of interest to medical applications. The beamline, between the ion source and the collection chamber, consists of ion extraction and focusing elements, and a dipole magnet mass spectrometer recovered from the LISOL facility in Louvain-la-Neuve. The latter has been modified for compatibility with MEDICIS, including the installation of a window for injecting laser light into the ion source for resonance photo-ionization. Ion beam optics and magnetic field modelling using SIMION and OPERA respectively were performed for the design and characterization of the beamline. The individual components and their optimal configuration in terms of ion beam extraction, mass separation and ion transport efficiency is described, along with details of the commissioning and initial performance assessment with stable ion beams.